Multi-decadal observations of the size structure of sperm whales at Kaikōura, New Zealand. Issue 1 (2nd January 2023) - Dickson, Toby; Rayment, William; Guerra, Marta; Dawson, Steve
ABSTRACT: Measurements of body length play an important role in the assessment of size and population structure of whales, allowing estimation of population parameters such as age at sexual and physical maturity. Uniquely, sperm whales can be measured from the interpulse interval (IPI) of their echolocation clicks, which contain information on the length of the head, which is allometrically related to body length. Measurements of IPI were taken from 424 acoustic recordings made between 1996 and 2019 at Kaikōura, New Zealand. Extrapolation to total length, using a new regression equation calculated from this population, revealed a significant increase in the mean length of whales visiting Kaikōura during summer in recent years (2014–2019), with no trend in the mean length for those visiting in winter. Increasing size during summer months appears to be driven by the growth of the same individuals returning summer after summer, combined with declining recruitment of new, smaller individuals. Thus, we hypothesise that the whales that visit in summer may represent an aging population. This is significant as sperm whales are a taonga [Of special significance to NZ Māori] species, top predators in the Kaikōura ecosystem, and the primary focus of the tourism industry at Kaikōura.